ANTI-INFLAMMATORY PROFILING OF SEED AND RIND EXTRACTS OF AMOMUM SUBULATUM - AGNIHOTRI, SUPRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The study aimed to evaluate the anti-inflammatory activity of Amomum subulatum (greater cardamom) seed and rind extracts in Wistar rats. Methods: The seed and rind of A. subulatum were air-dried in the shade, powdered, and subjected to 80% hydroalcoholic extraction in the Soxhlet apparatus. The anti-inflammatory activity of the seed and rind extracts of A. subulatum was evaluated by in vivo and in vitro methods. Results and Discussion: In vivo studies, namely, carrageenan-induced rat paw edema, cotton pellet granuloma, and formaldehyde-induced arthritis model confirmed the anti-inflammatory potential of seed and rind extracts of A. subulatum. It was found that rind extract exhibited better inhibition of inflammation as compared to seed extract. A. subulatum rind extract at the dose of 500 μg/ml exhibited best results for in vitro studies, namely, inhibition of albumin denaturation (73% inhibition), antiproteinase action (58% inhibition), membrane stabilization, heat-induced hemolysis, hypotonicity-induced hemolysis (54% inhibition), anti-lipoxygenase activity. Conclusions: The results of the study showed that the rind extract of A. subulatum (greater cardamom) possesses significant anti-inflammatory potential in various in vivo and in vitro anti-inflammatory models in the experimental animals.